Patient and family perceptions of a discharge bedside board - D.E. McMillan; D.B. Brown; K.L. Rieger; G. Duncan; J. Plouffe; C.C. Amadi; S. Jafri (Elsevier, 2023)
Objective: To explore patient and family perspectives of a discharge bedside board for supporting engagement in patient care and discharge planning to inform tool revision. Methods: This qualitative descriptive study included 45 semi-structured interviews with a purposeful sample of English-speaking patients (n = 44; mean age 58.5 years) and their family members (n = 5) across seven adult inpatient units at a tertiary acute care hospital in mid-western Canada. Thematic (interviews), content (board, organization procedure document), and framework-guided integrated (all data) analyses were performed. Results: Four themes were generated from interview data: understanding the board, included essential information to guide care, balancing information on the board, and maintaining a sense of connection. Despite application inconsistencies, documented standard procedures aligned with recommended board (re)orientation, timely patient-friendly content, attention to privacy, and patient-provider engagement strategies. Conclusion: Findings indicate the tool supported consultation and some involvement level engagement in patient care and discharge. Board information was usually valued, however, perceived procedural gaps in tool education, privacy, and the quality of tool-related communication offer opportunities to strengthen patients' and families' tool experience. Innovation: Novel application of a continuum engagement framework in the exploration of multiple data sources generated significant insights to guide tool revision.